Memória e esquecimento para além do direito estatal - Dias, Juarez Sanfelice (2018)
The objective of this work is to study the existing conflict between memory and oblivion, with the aim of seeking the foundation for the existence of a right to be forgotten. Therefore, a multidisciplinary study will be done, starting from psychoanalysis, religion, philosophy and history, as well as the conflict will be analyzed from a broad meaning of law, which does not abandon the State law as the protagonist, but sees the other structural spaces of capitalist societies. We will depart from the approach and response by the State law to the conflicts to, at the end, seek an interaction with other existent right forms, especially the systemic right, the community's right and domestic's right, aiming a balance between memory and oblivion that presents effectiveness with emancipation